Territorial planning in Europe: New concepts, new experiences. - Novarina, Gilles; Zepf, Marcus (TH Zürich, NSL, 2009)
Nach einer kurzen Schilderung der Entwicklung der räumlichen Planung in Stadt-/Metropolregionen in der Geschichte der Planungsansätze einiger europäischer Länder (Italien, Vereinigtes Königreich, Frankreich, Deutschland) seit den 1960er Jahren, werden die Elemente des sich in den 1990er Jahren entwickelnden neuen Planungstyps, der sich innerhalb Europas in verschiedenen Variationen herausgebildet hat, beschrieben. Es handelt sich dabei immer um Planungsansätze, die räumliche (Planungs-)Grenzen (Stadt - Stadt-Region) überwinden, auf einer Verständigung zwischen den verschiedenen Akteuren beruhen und neue Planungsinstrumente entwickeln. Sie schaffen Verbindungen zwischen Plänen und Projekten, beteiligen die Zivilgesellschaft und betonen die Bedeutung des Prozesses gegenüber den Planungsinhalten.

European metropolises are facing numerous challenges: the influence of globalization on the local economy, the rising share of service-based activities (both for businesses and residents), the development of new information and communication technologies, an increase in mobility, the fragmentation of urban space, which goes against the principles of sustainable development, and the persistence of social and spatial segregation. In order to face such changes, new modes of governance have to be developed. Cities should be able to question the traditional division of roles between the various tiers of territorial government and to pool private as well as public sector resources. The concepts that until recently have underpinned urban planning or regeneration practices seem to be increasingly ill-adapted to the current situation. Many researchers have attempted to identify the characteristics of the new types of planning that emerged in the 1990s. By drawing from the theories of communicative action (Habermas) and of structuration (Anthony Giddens), they defined planning as an interactive process and insisted on the collaboration and cooperation that this particular type of governance activity implies. Their works give more weight to processes than to content. By suggesting a new concept, that of territorial planning, this paper examines new practices aimed at jointly dealing with issues related to the environment, mobility, urban regeneration and social cohesion within a new approach to planning.
Keywords: Stadtplanung; Stadtregion; Planungstheorie; Planungspraxis; Planungsinstrument; Raumplanung; Kooperation; Kommunale Zusammenarbeit; Plan; Planungsprozess; Steuerungsinstrument; Zivilgesellschaft; Akteur; Projekt; Entscheidung; Entgrenzung